Implementasi Fatwa DSN-MUI dalam Pengembangan Pasar Modal Syariah di Indonesia - Arifa Ilmiyati; Faiza Nadilah; Rohmatun Nazilah; Viki Malikhatuz Zakiyah; Muhammad Taufiq Abadi (CV. KAMPUS AKADEMIK PUBLISING, 2023)
The implementation of the Fatwa of the National Sharia Council-Indonesian Ulema Council (DSN-MUI) has a very significant impact on the sharia capital market in Indonesia. The aim of writing this article is to analyze the implementation of the DSN-MUI fatwa and its impact on the Islamic capital market in Indonesia. The research method used is a literature study which is carried out by discussing various literature studies required for the research. The results of the analysis carried out show that the implementation of the DSN-MUI fatwa has provided a strong sharia legal foundation for the development of the sharia capital market in Indonesia. The fatwa regulates several aspects, including sharia principles that must be adhered to by certain business entities that are involved in the sharia capital market. The visible impact is in the growth in the number of sharia financial products and instruments, as well as increasing investor interest in the sharia capital market. The implementation of the DSN-MUI fatwa has provided positive changes in the development of the sharia capital market in Indonesia. It is hoped that this research can provide a better understanding of the implementation of the DSN-MUI fatwa on the capital market in Indonesia and make a small contribution to the development of the sharia capital market in the future. Keywords: Sharia Capital Market, Fatwa, DSN-MUI